2009
DOI: 10.2307/27735903
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Opportunity in Adaptive Radiation of Galápagos Endemic Land Snails

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. abstract: The classic evolutionary hypothesis of ecological opportunity proposes that both heterogeneity of resources and freedom from enemies promote phenotypic divergence as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 41 publications
5
63
2
4
Order By: Relevance
“…Among birds, Galapagos mocking birds also appear to follow the progression rule (66), although Darwin's finches show limited evidence of diversification closely associated with the geological formation of the islands (2). A progression pattern has been inferred for Galapagos bulimulid land snails (67). In contrast, insects including Galapagos flightless weevils (Galapaganus) (68) and the microlepidopteran genus Galagete (69) do not follow the progression rule.…”
Section: The Progression Rule In Comparative Island Phylogeographymentioning
confidence: 99%
“…Among birds, Galapagos mocking birds also appear to follow the progression rule (66), although Darwin's finches show limited evidence of diversification closely associated with the geological formation of the islands (2). A progression pattern has been inferred for Galapagos bulimulid land snails (67). In contrast, insects including Galapagos flightless weevils (Galapaganus) (68) and the microlepidopteran genus Galagete (69) do not follow the progression rule.…”
Section: The Progression Rule In Comparative Island Phylogeographymentioning
confidence: 99%
“…As lineages diversify into multiple species, competition between newly formed species would intensify. Consequently, the diversification rate would decrease as species accumulate in the limited space (3,14). In this study, we use DNA sequence data and a variety of analytical methods to test whether the habitat shift of Gammarus promoted diversification rates.…”
mentioning
confidence: 99%
“…In the case of L. clamitans, there is very little diet variation between individuals and this small amount of variation may not be affected by ecological parameters. While ecological opportunity and its associated resource diversity increase IS in many species (Nosil and Reimchen 2005;Parent and Crespi 2009;Darimont et al 2009), our results combined with at least one other study demonstrated that it is not ecologically universal (Evangelista et al 2014).…”
Section: !supporting
confidence: 54%
“…For example, while most studies have found that IS is greater in areas that have more resources or a more heterogeneous habitat (Darimont et al 2009;Parent and Crespi 2009;Martin and Pfennig 2010;Matich et al 2011), some species do not respond to ecological opportunity and resource diversity in the same way (Evangelista et al 2014). When intraspecific competition is high, some studies found that IS increased Tinker et al 2012;Darimont et al 2009;Frédérich et al 2010) but others found that IS decreased (Jones and Post 2013;Parent et al 2014).…”
Section: !mentioning
confidence: 99%
See 1 more Smart Citation